Predictors of futile recanalization in basilar artery occlusion patients undergoing endovascular treatment: a post hoc analysis of the ATTENTION trial - Yi, Tingyu; Li, Kai; Lin, Xiao-hui; Lin, Ding-lai; Wu, Yan-Min; Pan, Zhi-nan; Zheng, Xiu-fen; Chen, Rong-cheng; Zeng, Guoyong; Chen, Wen-huo (Frontiers in Neurology, 2023)
Methods This is a post hoc analysis of ATTENTION trial (The Trial of Endovascular Treatment of Acute Basilar-Artery Occlusion, ClinicalTrials.gov, number NCT 04751708). Demographics, clinical characteristics, acute stroke workflow interval times, and imaging characteristics were compared between the futile recanalization and favorable recanalization groups. Favorable outcome was defined as 90-days’ mRS 0-3, successful reperfusion was defined as TICI 2b, and 3 on final angiogram, futile recanalization was defined as fail to achieve favorable outcome despite successful reperfusion. A multivariate analysis was performed to identify the predictors of futile recanalization. Results One hundred eighty-five patients were included in the final analysis; 89 (48.1%) patients had futile recanalization, and 96 (51.9%) patients had favorable recanalization. In the multivariable logistic regression analysis, older age (OR 1.04, 95% CI 1.01 to 1.08, P=0.01) and diabetes mellitus (OR 3.35, 95% CI 1.40 to 8.01, P=0.007) were independent predictors of futile recanalization. Conclusions Futile recanalization occurred in near half of patients with acute BAO following endovascular treatment. Old age and diabetes mellitus were identified as independent predictors of futile recanalization after endovascular therapy for acute BAO.